2016
DOI: 10.2500/ajra.2016.30.4290
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Chronic Rhinosinusitis: A Controlled Cohort Study

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 35 publications
4
63
1
Order By: Relevance
“…With regard to demographics, depression was associated with female sex in two studies, 8,19 whereas three studies failed to detect an association. 7,13,18 In general, other demographic factors, such as age and race, were uniformly not associated with depression. In addition, there were no comorbidities consistently associated with depression.…”
Section: Factors Associated With a Positive Depression Screen Results mentioning
confidence: 99%
See 3 more Smart Citations
“…With regard to demographics, depression was associated with female sex in two studies, 8,19 whereas three studies failed to detect an association. 7,13,18 In general, other demographic factors, such as age and race, were uniformly not associated with depression. In addition, there were no comorbidities consistently associated with depression.…”
Section: Factors Associated With a Positive Depression Screen Results mentioning
confidence: 99%
“…1). These studies include a total of 2774 adult patients with CRS, with six studies that used the American Academy of OtolaryngologyHead and Neck Surgery criteria, [7][8][9][10][11][12] four studies that used European Position Paper on Rhinosinusitis and Nasal Polyps criteria, [13][14][15][16] two studies that used both the American Academy of OtolaryngologyHead and Neck Surgery and the European Position Paper on Rhinosinusitis and Nasal Polyps criteria, 17,18 and one study that used physician diagnosis to determine CRS. 19 With regard to depression, there were no studies that used strict Diagnostic and Statistical Manual of Mental Disorders, 4th Edition criteria.…”
Section: Systematic Review Of a Positive Depression Screen Results Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Gregurić et al 4 review the differences of the Sino-Nasal Outcome Test 22 scores versus visual outcomes scales when comparing patients with and those without polyposis, which showed significant differences in health-related QOL between the two groups. Schlosser et al 5 investigated the growing recognition of the association between chronic rhinosinusitis (CRS) and other comorbidities; in this case, that of depression, which showed that depression may be more closely associated with CRS than previously realized and especially for patients with polyposis. DeConde and Soler 6 review the epidemiologic data that evaluates the burden of illness that CRS places on society and shows that, although clinicians are focused by guidelines on sinus-specific symptoms, patients seem to be most impacted by the general-health related consequences of CRS.…”
mentioning
confidence: 99%